The Internationalization of the Education Inspectorate in Catalonia. A New Perspective - Gonzalez Ramírez, Jordi; Melgar Alcantud, Ángel (Avances en Supervisión Educativa, 2026)
This article analyses the evolution of the internationalization of the Education Inspection in Catalonia as a strategic line formalized within the 2021-2025 Master Plan and with continuity in the 2025-2029 Master Plan. It details the six main lines of action, including participation in the Erasmus+ CETE+ consortium for the mobility of educational institutions and inspectors, active membership in the European association SICI to compare evaluation models, and the promotion of internationalization in schools. Furthermore, it highlights the awarding of an Erasmus+ KA2 project (2025-2028) focused on personalized learning and Artificial Intelligence, in collaboration with institutions from Portugal, Latvia, and Georgia. The text concludes that internationalization must be a planned and collective process, led by the Subdirectorate General of the Inspectorate, aimed at improving the quality and equity of the educational system through the exchange of international experiences.